Optical image encryption and authentication scheme with computational ghost imaging - Guo, Zhe; Chen, Su-Hua; Zhou, Ling; Gong, Li-Hua (Applied mathematical modelling, 2024)
•A new optical image encryption and authentication scheme is proposed with the computational ghost imaging.•The problem of inherent linear defect and key management in computational ghost imaging encryption system is solved.•The dual-channel encryption method provides multi-layer protection for the plaintext images. Considering the necessity of identity authentication in most scenarios, a dual-channel (digital channel and optical channel) image encryption and authentication algorithm with computational ghost imaging (CGI) is proposed. The entire encryption process is governed by the pseudo-random sequences obtained by the 4D chaotic system and the Logistic map. During the digital channel encryption, the confusion and diffusion of the plaintext image are achieved by random scrambling and DNA computing, respectively. To alleviate the burden of key transmission and storage in the CGI encryption system, the speckle measurement matrices are constructed with the pseudo-random numbers obtained by the Logistic map. Additionally, a nonlinear encryption operation is carried out to compensate the linear vulnerability of CGI encryption. In the optical encryption channel, the authentication image is first encrypted with the CGI method, followed by the secondary encryption of the intensity values recorded by a bucket detector to produce an intermediate ciphertext. The final encryption image is generated by merging the intermediate ciphertexts from both encryption channels. It is demonstrated that the proposed optical image encryption and authentication scheme with CGI provides satisfactory encryption and decryption effects and can effectively counteract the common attacks. Moreover, the scheme holds promising application prospects due to its authentication capability.